Tri Prasetyo Utomo DESAIN AROMATHERAPY DECORATIVE LIGHT DENGAN LAMPU ULTRAVIOLET DAN MINYAK ATSIRI - Tri Prasetyo Utomo; Eko Sri Haryanto (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
The lamp is one of the elements of interior conditioning, aromatherapy decorative lights in addition to beingused as lighting, can also be used to create an interior atmosphere. Aromatherapy decorative lights can bedeveloped into other functions that can support the activities of human needs in the interior, some of which arefor health and comfort. This artistic research is intended to make lighting products using wood that has notbeen utilized to the full. This artistic research is also trying to develop other materials which are still rarely usedoptimally, namely ultra violet lamps and essential oils. Essential oils are available in many tropical environmentswhile this is only used by the community as a medicinal ingredient and cooking spice. This artisticresearch activity begins with product discovery until innovation results are obtained in the product designprocess. The first stage in this published research is to determine the objects needed then conduct analysisand synthesis, then carry out the planning process in accordance with the needs of recovery, health andcomfort. This artistic creation is also trying to utilize the pallet wood waste that is commonly found at loadingand unloading locations of freight forwarding which is then combined with sonokeling wood as the main materialof the lamp. The results of this artistic study consist of several designs of Aromatherapy Decorative Lampsthat are used as room lighting elements, decorative elements and as aromatherapy media. The results of thisartistic research are also expected to provide sifting on the material for the MK Interior Design and MK. InteriorAccessories Design in the Interior Design Study Program at the Indonesian Art Institute in Surakarta.